Emergency department presentation and mortality rate due to overdose: A retrospective cohort study on nonfatal overdoses. Issue 4 (1st October 2016) - Pavarin, Raimondo Maria; Berardi, Domenico; Gambini, Daniele
ABSTRACT: Background: The aims of this retrospective cohort study are to describe the presentation characteristics for nonfatal overdose-related complaints at the emergency departments (EDs) of the metropolitan area of Bologna (northern Italy), to estimate the subsequent risk of mortality by overdose, and to identify the profiles of the subjects most at risk. Methods: Records of patients admitted to 10 EDs for overdose between January 2004 and December 2012 were retrospectively evaluated. The International Classification of Diseases was used to ascertain the cause of death. Results: A total of 294 episodes of overdose involving 218 individuals were identified. The total time at risk was 1048 person-years (PY). The mortality rate for all causes was 35.48 per 1000 PY for males and 20.61 per 1000 PY for females. The mortality rate for overdose was 16.6 per 1000 PY for males and 13.74 per 1000 PY for females. In the multivariate regression analysis, the time from first ED overdose access (less than 1 year risk ratio [RR]: 7.07, 95% confidence interval [CI]: 5.32–9.39) was significantly associated with death by overdose. Males, subjects aged >30 years at presentation, patients who refused ED treatment, and those having previously contacted mental health services showed an increased mortality risk due to overdose. Conclusions: Experiencing a nonfatal overdose within the past 12 months increases the risk of mortality compared with an overdose more than 12 months earlier. Nonfatal overdose patients presenting to an ED form a specific target for prevention projects.